Some basic psychological traits for amateur Algerian Football players - Toufik ben salem (Social Empowerment Journal, 2023)
This study aimed to identify the most important psychological characteristics that must be available to amateur Football players in the middle category, especially those that are focused on in the process of psychological sports preparation to enhance the sports personality and its effectiveness in achieving directed goals in the field of Football, where the researcher relied on the descriptive approach. The questionnaire forms were distributed to amateur football players, and the study sample consisted of 70 seventy athletes, most of whom are amateur football clubs in the state of Djelfa, who are active at the local municipal level. One of the most important results of the study is that the basic psychological traits classified by the researcher (the trait of self-confidence - the trait of focusing attention), which the coaches focus on developing in the personality of the players and urging them to acquire them in order to achieve mental toughness and psychological balance, which results in better performance in training and competition.